2005
DOI: 10.1590/s0102-311x2005000200006
|View full text |Cite
|
Sign up to set email alerts
|

Acesso à consulta a portadores de doenças sexualmente transmissíveis: experiências de homens em uma unidade de saúde de Fortaleza, Ceará, Brasil

Abstract: Access to healthcare services is one of the important aspects of the Unified National Health System in Brazil, and the supply and management of such services is the responsibility of municipalities. This study focuses on difficulties faced by men with sexually transmitted diseases (STDs) in accessing appointments for treatment. This was a qualitative study of men treated at an STD clinic in Fortaleza, Ceará State, Brazil, in November 2003, using content analysis technique and interpretation of interviews, focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
15

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 5 publications
(7 reference statements)
0
10
0
15
Order By: Relevance
“…Looking at the collective health/public health literature, it was confirmed that men's access to, or better yet, difficulty in accessing health services is a relevant concern (Schraiber et al, 2010;Couto et al, 2010;Toneli et al, 2010;Pinheiro and Couto, 2008;Nascimento and Gomes, 2008;Gomes et al, 2007;Paschoalick et al, 2006;Araújo and Leitão, 2005), and this is one of PNAISH's main objectives. Schraiber et al (2010) stress that Atenção Primária a Saúde (Primary Care: APS) -the main access point to health services -is markedly aimed at women's health problems, as prevention and health care are socially characterized as essentially female tasks.…”
Section: Men's Health and Masculinitiesmentioning
confidence: 99%
“…Looking at the collective health/public health literature, it was confirmed that men's access to, or better yet, difficulty in accessing health services is a relevant concern (Schraiber et al, 2010;Couto et al, 2010;Toneli et al, 2010;Pinheiro and Couto, 2008;Nascimento and Gomes, 2008;Gomes et al, 2007;Paschoalick et al, 2006;Araújo and Leitão, 2005), and this is one of PNAISH's main objectives. Schraiber et al (2010) stress that Atenção Primária a Saúde (Primary Care: APS) -the main access point to health services -is markedly aimed at women's health problems, as prevention and health care are socially characterized as essentially female tasks.…”
Section: Men's Health and Masculinitiesmentioning
confidence: 99%
“…Pode também estar associada à visão que os homens têm em relação à saúde, pois atribuem à mulher a responsabilidade pelo cuidado 23,24 . Por outro lado, existem ainda questões inerentes aos serviços 21,25 e ao comportamento dos parceiros, como é o caso do uso de drogas e álcool 26 .…”
Section: Discussionunclassified
“…Buscando colocar em pauta o tema saúde do homem a PNAISH (Brasil, 2008) aponta estudos (Araújo & Leitão, 2005;Gomes, Nascimento & Araújo, 2007;Gomes, Nascimento, Rebello & Araújo, 2008) que evidenciaram algumas justificativas para a ausência de homens nos serviços de saúde, sendo estas alocadas em dois grupos principais de determinantes, aqueles que se estruturam como barreira institucional e os de natureza sociocultural. Ilustrando um pouco mais essas barreiras, têm-se o horário de funcionamento dos serviços que coincidem com o horário de trabalho, o tempo de espera para atendimento e profissionais de saúde, em sua grande maioria pertencente ao sexo feminino, como elementos constituintes da barreira institucional.…”
Section: Introductionunclassified